A miniaturized 4 K platform for superconducting infrared photon counting detectors. (29th September 2017) - Gemmell, Nathan R; Hills, Matthew; Bradshaw, Tom; Rawlings, Tom; Green, Ben; Heath, Robert M; Tsimvrakidis, Konstantinos; Dobrovolskiy, Sergiy; Zwiller, Val; Dorenbos, Sander N; Crook, Martin; Hadfield, Robert H
Abstract: We report on a miniaturized platform for superconducting infrared photon counting detectors. We have implemented a fibre-coupled superconducting nanowire single photon detector in a Stirling/Joule–Thomson platform with a base temperature of 4.2 K. We have verified a cooling power of 4 mW at 4.7 K. We report 20% system detection efficiency at 1310 nm wavelength at a dark count rate of 1 kHz. We have carried out compelling application demonstrations in single photon depth metrology and singlet oxygen luminescence detection.